Production of soluble and active microbial transglutaminase in Escherichia coli for site‐specific antibody drug conjugation. (26th December 2015) - Rickert, Mathias; Strop, Pavel; Lui, Victor; Melton‐Witt, Jody; Farias, Santiago Esteban; Foletti, Davide; Shelton, David; Pons, Jaume; Rajpal, Arvind
Abstract: Applications of microbial transglutaminase (mTGase) produced from Streptomyces mobarensis ( S. mobarensis ) were recently extended from food to pharmaceutical industry. To use mTGase for clinical applications, like generation of site specific antibody drug conjugates, it would be beneficial to manufacture mTGase in Escherichia coli ( E. coli ). To date, attempts to express recombinant soluble and active S. mobarensis mTGase have been largely unsuccessful. mTGase from S. mobarensis is naturally expressed as proenzyme and stepwise proteolytically processed into its active mature form outside of the bacterial cell. The pro‐domain is essential for correct folding of mTGase as well as for inhibiting activity of mTGase inside the cell. Here, we report a genetically modified mTGase that has full activity and can be expressed at high yields in the cytoplasm of E. coli . To achieve this we performed an alanine‐scan of the mTGase pro‐domain and identified mutants that maintain its chaperone function but destabilize the cleaved pro‐domain/mTGase interaction in a temperature dependent fashion. This allows proper folding of mTGase and keeps the enzyme inactive during expression at 20°C, but results in full activity when shifted to 37°C due to loosen domain interactions. The insertion of the 3C protease cleavage site together with pro‐domain alanine mutants Tyr14, Ile24, or Asn25 facilitate high yields (30–75 mg/L), and produced an enzyme with activity identical to wild type mTGase from S. mobarensis . Site‐specific antibody drug conjugates made with the E .coli produced mTGase demonstrated identical potency in an in vitro cell assay to those made with mTGase from S. mobarensis .